Tuberculosis around the tarsal navicular: A rare entity. (August 2016) - Vijay, Vipul; Gupta, Nishint; Vaishya, Raju
Highlights: Three cases of tubercular infection around the tarsal navicular are presented with different presentation. The key to good results is high index of suspicion and obtaining tissue for histo-pathological examination. Good functional results can be expected if the diagnosis is achieved early and adequate anti-tubercular therapy is given. Abstract: Osteoarticular TB around the tarsal navicular is a chronic, uncommon condition affecting the midfoot, which causes significant morbidity to the patient. Tuberculosis around the tarsal navicular is rarely described in the literature. A series of three cases – two involving the talo-navicular joint and one involving the naviculo-cuneiform joint is described. Biopsy was used in all the cases for achieving diagnosis. All patients had good to fair outcome following medical management with anti-tubercular therapy. Due to the pauci-bacillary nature of the disease, a positive culture of the disease is not always possible. The diagnosis depends on a positive histopathology finding. Once an early diagnosis is achieved, antitubercular therapy is usually the mainstay. Clinical awareness of the rare presentations of this disease can help in early detection, adequate treatment and good to fair outcomes. Due to the destruction of the midfoot joints, some patients report difficulty in walking on uneven surfaces and barefoot, for which triple arthrodesis may be offered.